The education of a WASP - Stalvey, Lois Mark (Wisconsin studies in American autobiography., 1989)
Brimming with honestly and passion, The Education of a WASP chronicles one white woman's discovery of racism in 1960s America. First published in 1970 and highly acclaimed by reviewers, Lois Stalvey's account is as timely now as it was then. Nearly twenty years later, with ugly racial incidents occurring on college campuses, in neighborhoods, and in workplaces everywhere, her account of personal encounters with racism remains deeply disturbing. Educators and general readers interested in the subtleties of racism will find the story poignant, revealing, and profoundly moving. "Delightful and horrible, a singular book."--Choice "An extraordinarily honest and revealing book that poses the issue: loyalty to one's ethnic group or loyalty to conscience."--Publishers Weekly